USE OF METHODOLOGICAL TRIANGULATION OF QUALITATIVE RESEARCH INVESTIGATING THE LIMITS OF LIFESTYLE IN CHRONICALLY ILL PATIENTS BASED ON USING OF NURSING DIAGNOSES DOMAINS - Chrastina, Jan; Ivanová, Kateřina (Profese Online, 2010)
Research of lifestyle in chronically ill is demanding and research- extensive scientific area in nursing. It requires sufficient experience of the researcher, knowledge of the research problem both in theoretical framework and research methodology. Research surveys identifying and describing lifestyle with the chronic disease may be focused on uncovering potential limits according to the chronic disease. In nursing, knowledge of chronic diseases and its limits of lifestyle in patients are very important, especially for so-called civilization diseases. Quantitative study don't bring a deep understanding of the problem, and therefore qualitative research is recommended. To support validity of nursing qualitative research, triangulation method is often used. Summarization of possible types of triangulation is defined and described in tab. 1. "The limits of the lifestyle in chronically ill patients based on nursing diagnostic domains" is qualitative research, which is focused on find out and describe limits of the lifestyle in patients suffer from selected chronic diseases - sclerosis multiplex, selected psychiatric diagnosis and diabetes mellitus. Based on identification of these limits, implementation into nursing diagnosis domains can be possible. This project has been using specific methodological triangulation, using three methods - unstructured interview, the life story method (including the life curve describing method), and "The Cantrill's Ladder" method. As so called "research milestones" in nursing research, diagnosis domains of selected taxonomies can be used too. In our research, classification systems of "NNN Alliance" are be used. Using of content analysis of nursing diagnoses of nursing classification systems can also be used.
Keywords: lifestyle; limits of lifestyle; chronic disease; qualitative research; triangulation; nursing diagnoses domains